2001
DOI: 10.1002/jmv.2066.abs
|View full text |Cite
|
Sign up to set email alerts
|

Shift in predominating subtype of HCV from 1b to 3a in St. Petersburg mediated by increase in injecting drug use

Abstract: The genotypes of 149 HCV strains from St. Petersburg were determined by limited sequencing and phylogenetic analysis within the NS5B region. One hundred two strains derived from patients that attended infectious disease clinics, of whom 48 admitted injecting drug use, and 47 derived from dialysis patients. Subtype 3a was predominant in the patients from infectious disease clinics, both in patients that admitted injecting drug use (56%) and in those with unknown source of infection (46%). However, 89% of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…Particular HCV subtypes have been shown to be associated with injecting drug use in Western Europe 10–14 . This phenomenon has also been observed in central and Eastern Europe, where the size of the illicit drug market increased after political changes took place in 1989 15–17 . These results suggest that infection with a particular HCV genotype or subtype is spreading and is potentially being accumulated among IDUs.…”
Section: Introductionmentioning
confidence: 79%
“…Particular HCV subtypes have been shown to be associated with injecting drug use in Western Europe 10–14 . This phenomenon has also been observed in central and Eastern Europe, where the size of the illicit drug market increased after political changes took place in 1989 15–17 . These results suggest that infection with a particular HCV genotype or subtype is spreading and is potentially being accumulated among IDUs.…”
Section: Introductionmentioning
confidence: 79%
“…In Eastern Europe and Russia, genotype 1a was more prevalent in the general population prior to the epidemic of HCV among drug injectors, but 3a appears to have outstripped 1a in younger people and IDUs (60-63). In a study of hundred and two patients who attended infectious disease clinics in St. Petersburg, subtype 3a was predominant in the patients reporting injecting drug use (56%) and in those with unknown source of infection (46%) (20). The authors concluded that the previously dominant subtype 1b was being replaced by subtype 3a in St. Petersburg mediated through an increased in injection drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Among its population of 4.5 million, an estimated 30,000 to 80,000 inject drugs and more than 35,000 diagnosed HIV cases have been documented (17, 18). However, since less is known about the extent of HCV infection and the scant published data are more than half a decade old (19, 20), better data are needed on the extent of the HCV epidemic among injectors in the city and its spread through networks of injectors. Toward this end, we assembled a sample of active IDUs in St. Petersburg using a chain referral method known as respondent driven sampling (RDS) that is widely considered best suited for obtaining reliable sampling of hidden populations such as IDUs (21, 22).…”
Section: Introductionmentioning
confidence: 99%
“…Another study with German patients showed that subtype 1b was predominant among elderly patients, while subtype 1a was predominant among the younger population (26). A third study with Russian patients showed that subtype 1b was progressively replaced by subtype 3a (14). Past studies have shown that the main risk factor for infection by genotypes 1a and 3a is intravenous drug use (10,18,35) and that the main risk factor for infection by genotypes 1b and 2 is blood transfusion (10,18).…”
Section: Discussionmentioning
confidence: 99%